Veterinary Pharmacovigilance: A Review of Systems in France, USA and India - Yash Raghuwanshi; Nikita Khule; Virendra Ligade (The Indian Veterinary Journal, 2023)
Pharmacovigilance is an integral part of the healthcare system similarly; PV (Pharmacovigilance) for veterinary aspects is also a relatively new but emerging concept. It is gaining importance as animal-based food products are consumed by humans and there have been reports of adverse events in humans due to exposure to veterinary products such as hypersensitivity reactions, nausea dizziness, and adverse effect of veterinary products on the environment like decrease in vulture population due to diclofenac administered in cattle which were later consumed by vultures causing toxicity and death. In this paper, we have reviewed systems in France and USA and current scenarios in India and emphasized on the importance of having such a system in India, which is still lacking. An efficient Veterinary PV system is required in India due to ever growing of new veterinary pharmaceuticals entering the market.